Technical Feasibility of Acoustic Coordinated Reset Therapy for Tinnitus Delivered via Hearing Aids: A Case Study - Christian Hauptmann; Mark Williams; Federica Vinciati; Markus Haller (Case Reports in Otolaryngology)
Primary tinnitus has a severe negative influence on the quality of life of a substantial portion of the general population. When acoustic coordinated reset (CR) neuromodulation stimuli are delivered for several hours per day over several weeks a clinically significant symptom reduction in patients with primary tonal tinnitus has been reported by several clinical sites. Here, we reported the first case where CR neuromodulation was delivered through a hearing aid. A 52-year-old man with chronic primary tonal tinnitus was previously considered untreatable with sound therapy. He initially received the classic CR treatment protocol with signals delivered with the separate proprietary device with his hearing aids removed during treatment. He was subsequently treated with the therapy being deployed through a set of contemporary hearing aids. After 5 months of classic CR treatment with the separate custom device, the THI and VASL/A scores worsened by 57% and 13%/14%, respectively. Using the hearing aid without CR treatment for 5 months no change in tinnitus symptoms was observed. However, after three months of CR treatment delivered through the hearing aids, the THI and VASL/A scores were reduced by 70% and 32%/32%, respectively.